2005
DOI: 10.1111/j.1467-8535.2005.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Netskills and the current state of beliefs and practices in student learning: an assessment and recommendations

Abstract: This article analyses data from over 1000 student questionnaires dealing with how students currently use the web to support their learning. It discusses student understanding, needs, and expectations of the web and the overwhelming perception that the web now forms an integral part of their study and research practices. However, these practices require greater definition and refinement for and by the student. Evidence from some teaching staff is compared with that from students for validation purposes and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In this study, survey and interview results further confirmed the diversity of use and engagement with technology across the Emirati student population; this finding can further assist in the avoidance of an overestimation of student preparedness for utilizing such technologies in their coursework that has been found in other countries Messineo & DeOllos, 2005;Murray et al, 2005;Pedro, 2009). As pointed out by , "the question [remains] as to whether students' everyday skills with emerging technologies will correspond to skills associated with beneficial, technology based learning" (p. 119).…”
Section: )supporting
confidence: 49%
See 1 more Smart Citation
“…In this study, survey and interview results further confirmed the diversity of use and engagement with technology across the Emirati student population; this finding can further assist in the avoidance of an overestimation of student preparedness for utilizing such technologies in their coursework that has been found in other countries Messineo & DeOllos, 2005;Murray et al, 2005;Pedro, 2009). As pointed out by , "the question [remains] as to whether students' everyday skills with emerging technologies will correspond to skills associated with beneficial, technology based learning" (p. 119).…”
Section: )supporting
confidence: 49%
“…While a high majority of students consider themselves to be very skilful in searching, evaluating or utilizing the Internet (for example 81% of tertiary students in the US (Smith & Caruso, 2010)), certainly world-wide there is continued evidence that most students are generally not highly skilled or confident in their use of digital technologies (Cheong, 2008;Combes, 2008;Hargittai & Hinnant, 2008;Li & Ranieri, 2010;Margaryan et al, 2011;Metzger & Flanagin, 2008;Murray, Hourigan, Jeanneau, & Chappell, 2005;Rowlands, Nicholas, Williams, Huntington, & Fieldhouse, 2008;Selwyn, 2008b;Trinder et al, 2008).…”
Section: Claims Made About Digital Nativesmentioning
confidence: 99%
“…For example, it is now widely recognized that students' computer literacy needs to be addressed by language teachers when new technology is introduced and that students might therefore have to be trained to use this new technology (Barette, 2001;Taylor & Gitsaki, 2004). Murray, Hourigan, Jeanneau, and Chappell (2005) surveyed over 1,000 students on their use of the Web. Almost all students recognized the importance of using the Internet as a learning resource and reported that they did not need encouragement to use it in their studies.…”
Section: Student Perceptions Of Computer-based Language Activitiesmentioning
confidence: 99%
“…' Indeed, the online environment places greater and different burdens on tutors, for as a recent survey suggests, students 'count on the lecturers to be aware of the content of websites and to recommend them for their value as learning tools.' 7 At the same time, tutors are expected to be the early adopters and implementers of new educational technologies such as videoconferencing and to appear to be the 'experts' in such applications.…”
Section: Tutor-lite or Tutor-plight?mentioning
confidence: 99%
“…In this context it is worth noting the following observation from a recent netskills survey: 7 'Whilst the majority may have the necessary skills for using the web for recreational purposes, the idea of accessing this virtual setting for learning emerges as a crucial issue.' 7 This despite the fact that over 65% of respondents to the survey claimed they had used the web for more than three years! The survey's observation is sup ported by the comment that 'Students are actively involved in arranging their sports and social activities, but not their learning environments!'…”
Section: Technical Supportmentioning
confidence: 99%